The impact of personality traits on the return of major depression: a case–control study - Altaweel, Nada; Upthegrove, Rachel; Marwaha, Steven (Frontiers in Psychology, 2025)
BackgroundMajor depression is a common, chronic, recurrent, debilitating disorder. Despite effective treatments, remission rates remain low, and many of those who do experience remission then relapse. Some personality traits are potential risk factors for relapse, though they have, to date, received insufficient attention. There is growing attention to the role of emotional dysregulation in recurrent depression. We aimed to investigate the association between the return of major depression and emotional dysregulation, affective lability, and impulsivity personality traits.MethodA case–control design sampling adults over 18 years old with a history of depression and currently either experiencing a depressive episode (cases) or currently being free of a depressive episode (controls). Current depression was assessed using the Patient Health Questionnaire-9, and study participants were recruited online. Multi-staged logistic regression modelling was used to explore the association between personality traits and the return of depression, adjusting for important confounding factors.ResultsOne hundred fifty two respondents (76 cases and 76 controls) were recruited. Emotional dysregulation was significantly associated with the return of depression (OR = 1.03, 95% CI [1.00–1.06], p = 0.04) even after adjustment for the confounding factors: marital status and childhood trauma. Childhood trauma (OR = 1.04, 95% CI [1.00–1.08], p = 0.03) and being widowed, divorced, or separated (OR = 13.95, 95% CI [1.16–166], p = 0.03) were also associated with the return of depression. Our analysis did not detect any association between affective lability and impulsivity and the return of depression.LimitationsOur study relied on self-report questionnaires, including measuring depression. We used cross-sectional data in the present study analysis.ConclusionOur findings suggest emotional dysregulation and childhood trauma could work as risk factors and predate depression. This information can be used to develop targeted treatment plans and improve therapeutic outcomes.